The School Principal’s Situational Leadership Role, Supporting Factors and Its Impact: A Literature Review - Usman Usman; Bujang Rahman; Atik Rusdiani (Universitas Muhammadiyah Enrekang, 2024)
The Role of Situational Leadership of School Principals, Supporting Factors and Their Impact is a scientific article which aims to determine the role of situational leadership of school principals, supporting factors and their impact. The method for writing this Literature Review article is the literature review research method, sourced from Google Scholar with a period of 2019-2024. The results of this Literature Review article are that: 1) The Role of School Principals' Situational Leadership, 2) Supporting Factors for School Principals' Situational Leadership 3) Impact on School Principals' Situational Leadership.